The Development of Integrative Model for the Teaching of Indonesian Technical Vocabulary - Aziez, Furqanul (EDUCARE, 2008)
ABSTRACT: The main concern of this research is to develop a teaching model which can promote studentsâ vocabulary knowledge, especially the qualitative knowledge of the technical vocabulary. The problems underlying the research is that, despite its significance in language learning,Â  vocabulary is methodologically neglected.This is especially true to the teaching of teachnical words. On that basis, this study sets out to generate a teaching model which is effective in boosting studentsâ qualitative knowledge of technical vocabulary through a set of learning activities commensurate with the curricular requirements, namely, which deems language as a means of communication, which puts students in the core of all concerns and activities, and above all which is applicable for any classroom settings. Another result shows that despite its curricular demand, vocabulary is not taught by the teachers, while the teaching practice for other language areas is still dominated with the teacher-centered activities. The validation test results in significant finding: the model proves effective in evolving studentsâ qualitative vocabulary knowledge in the experimental class. In other words, the model is effective in teaching the Indonesian technical vocabulary.KEY WORDS: integrative, model, technical vocabulary, qualitative knowledge, and quantitative knowledge.About the Author: Dr. Furqanul Aziez is a lecturer at the Muhammadiyah University of Purwokerto (UMP) in Central Java; and also at Pasundan University (UNPAS) in Bandung. He is interested in education and applied linguistics. His email address is: furqonaziez2007@yahoo.co.idÂ How to cite this article? Aziez, Furqanul. (2008). âThe Development of Integrative Model for the Teaching of Indonesian Technical Vocabularyâ in EDUCARE: International Journal for Educational Studies, Vol.1(1) August, pp.53-66. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 7, 2008); Revised (July 17, 2008); and Published (August 17, 2008).